Diagnóstico de la confiabilidad de servicio y su relación con el comportamiento eléctrico de los transformadores de distribución del alimentador Tambo, subestación Pelileo de la Empresa Eléctrica Ambato S.A. (EEASA), durante el año 2016. Propuesta de repotenciación de centros de transformación, redes primarias y secundarias. - Gómez Cevallos, Juan Carlos (2017)
This research study shows the problem caused by the incidence of the electrical behavior of the distribution transformers in the electrical service reliability of ‘Tambo’ feeder in Pelileo substation of ‘Empresa Electrica Ambato S.A. (EEASA)’, during the year 2016. It was established through CONELEC 004/01 current regulation in the country, as well as works, papers and scientific journals related to the quality of technical service an adequate evaluation of the electrical system of the feeder. Through the field research and the help of measurement equipment such as energy analyzers, clamp current sensor, Siscp and Dataview software, was possible to obtain the information of electrical variables such as apparent power, grounding resistance, voltage, flicker, harmonic distortion in voltage, power factor establishing direct contact with reality without a manipulation of data. The methodology was both deductive and inductive. The first method was used from general principles for the measurement of parameters and the second one from the particular study of the electrical variables in order to determine in general the behavior of the feeder. In addition, an economic evaluation regarding the cost of the project implementation was made. Finally, the results were established through a Pareto chart and they determined that primary Tambo has the most critical variables to be solved with 59 load centers. It means that a 17% requires an urgent replacement, 259 grounded that represents a 76% do not comply with the regulations and 20 transformers identified with low power factor. Furthermore, regarding the economic analysis, for the implementation of the proposal requires an investment of 152 159, 13 dollars.